2022
DOI: 10.3233/jad-215506
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Imaging Determinants of Neurocognitive Disorders in Post-Acute COVID-19 Patients with Cognitive Complaints

Abstract: Background: Neurocognitive disorders (NCDs) are a part of the post-acute coronavirus disease (COVID-19) syndrome. No study has specifically evaluated NCDs in post-acute COVID-19 patients with cognitive complaints or their MRI determinants. Objective: To characterize NCDs in post-acute COVID-19 patients with cognitive complaints. The secondary objectives were to assess their clinical and MRI determinants. Methods: We included 46 patients with a post-acute COVID-19 cognitive complaint referred to the Amiens Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
(77 reference statements)
0
15
0
Order By: Relevance
“…Further supporting the notion of brain involvement in COVID-19 survivors, a higher prevalence and volume of White Matter Hyperintensities (WMH) seem to be a common finding among subjects who recover from the illness with residual cognitive impairments or depressive symptomatology ( Andriuta et al, 2022 , Cecchetti et al, 2022 , Hellgren et al, 2021 , Poletti et al, 2022 ). Finally, a diffusion microstructure imaging study comparing post-COVID subjects exhibiting neurological symptoms or cognitive impairment and healthy controls, found evidence of redistribution of water molecules with widespread decreasing intra-axonal and extra-axonal volume and increasing free water/CSF fractions in COVID-19 survivors; the magnitude of V-CSF-increase was found to correlate with the degree of cognitive impairment, and speculated by the authors to be reflective of vasogenic edema ( Rau et al, 2022 ).…”
Section: Discussionmentioning
confidence: 80%
“…Further supporting the notion of brain involvement in COVID-19 survivors, a higher prevalence and volume of White Matter Hyperintensities (WMH) seem to be a common finding among subjects who recover from the illness with residual cognitive impairments or depressive symptomatology ( Andriuta et al, 2022 , Cecchetti et al, 2022 , Hellgren et al, 2021 , Poletti et al, 2022 ). Finally, a diffusion microstructure imaging study comparing post-COVID subjects exhibiting neurological symptoms or cognitive impairment and healthy controls, found evidence of redistribution of water molecules with widespread decreasing intra-axonal and extra-axonal volume and increasing free water/CSF fractions in COVID-19 survivors; the magnitude of V-CSF-increase was found to correlate with the degree of cognitive impairment, and speculated by the authors to be reflective of vasogenic edema ( Rau et al, 2022 ).…”
Section: Discussionmentioning
confidence: 80%
“…A study by Apple et al 62 used a Z score of < −1 as the definition of cognitive impairment, when people with Z scores of −1.5 to −1 could be considered within the lower end of normal. Similarly, a study by Andruita et al 63 reported multiple domain cognitive dysfunction even though none of the domains reached a mean Z score of less than −1, meaning they still remain within normal limits.…”
Section: Long‐term Neurological Complications Of Covid‐19mentioning
confidence: 78%
“…The seven studies which have investigated the long-term effects of COVID infection (9 to 12 months) found a deterioration of cognitive performance in different cognitive domains, such as in overall cognition [ 91 ], memory [ 90 , 92 , 93 , 94 ], attention [ 95 , 96 ], executive functions [ 90 , 92 ] and visuospatial abilities [ 90 ].…”
Section: Resultsmentioning
confidence: 99%